Permasalahan Hukum Pembiayaan Leasing di Indonesia - Nahrowi Nahrowi (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2013)
Financing Leasing Legal Issues in Indonesia. Leasing as a financing model attract many businessmen to develop their business. As an alternative, financing for companies to raise capital by acquiring several advantages is as a model of financing. The involvement of multiple parties to the lease agreement, the lessor as the party hired to try to object lease, the lessee as a tenant, as a supplier of goods and banks as financiers, in the course of time when the execution of the agreement sometimes face legal issues. The issue of capital is also an obstacle to the development of leasing, for the lessor of course. These conditions need to be noticed in order to make leasing as an alternative financing for business activities in Indonesia that it can develop. DOI: 10.15408/jch.v1i1.2978